Influence of gold nanorods on the structure and photonic bandgap in a twist grain boundary phase with smectic C* blocks - Sahoo, Rajalaxmi; Rao, D. S. Shankar; Hiremath, Uma S.; Yelamaggad, V. C.; Shinde, Pravin; Bhagavatula L. V. Prasad; Prasad, S. Krishna (Journal of Molecular Liquids, 2020)
We describe the first report of the influence of gold nanorods (GNR) on the induced twist grain boundary smectic C* (TGBC*) phase in a binary mixture of achiral bent-core and chiral linear liquid crystals. The GNR concentration-dependent phase diagram of these nanocomposites shows that the thermal range of this twist grain boundary phase having smectic C* blocks phase increases by 50% for an intermediate composition compared to that for the host binary mixture without nanorods. The inclusion of the nanorods is seen to have substantial effect on the structural and photonic bandgap features of the TGBC* phase. For example, the helical periodidty gets altered in all the three dimensions: while those within the block undergo a huge increase, the one which is orthogonal to the blocks, shrinks. The spacing of the square grid pattern arising normal to the TGB helix direction increases for the nanocomposites getting even doubled for a certain composition, a feature evidenced by optical microscopy as well as optical diffraction. Xray diffraction clearly brings out the feature that the presence of GNR alters the thermal character of the transition between the TGBC* and the cholesteric phase. Quantitative analysis of the data indicates that the system would remain in the vicinity of a possible tricritical point, a behavior having wider ramifications to understand the underlying critical phenomenon. Based on the experimental observations, and capturing the essence of the reported adaptive defect core targeting mechanism we propose a model wherein GNRs get confined in the grain boundary region. This feature offers a potential to have periodic and anisotropic plasmonic structure arising out of the synergetic interactions between the metal nanorod and the twisted grain boundary structure. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: 3D photonic bandgap; Gold nanorods; Induced phase; TGBC* phase; Tricritical phenomena

Wide thermal range, exclusive occurrence of technically significant chiral nematic phase: synthesis and mesomorphism of cholesterol-based non-symmetric dimers - Nayak, Rashmi Ashwathama; Bhat, Sachin A.; Rao, D. S. Shankar; Yelamaggad, V. C. (Bulletin of Materials Science, 2020)
Fifteen new non-symmetric chiral dimers belonging to three different series have been synthesized and evaluated for their mesomorphic properties. They are formed by interlinking cholesterol with salicylaldimine (SAN) cores (with reverse imine groups) via an omega-oxyalkanoyloxy spacer. Within a series, the length of the terminaln-alkoxy tails has been varied for a fixed even-parity spacer. Three even-parity spacers such as 4-oxybutanoyloxy, 6-oxyhexanoyloxy and 8-oxyoctanoyloxy have been used to join two cores, whereas the terminal tails such asn-butyloxy,n-hexyloxy,n-octyloxy,n-decyloxy andn-dodecyloxy chains have been attached to the SAN core. Microscopic and calorimetric experimental results show that all the dimers behave identically exhibiting the chiral nematic (N*) phase solely, which was authenticated by powder X-ray diffraction studies carried out on some selected samples. In the vast majority of the cases, this phase is thermodynamically stable, and while cooling, it exists over a wide thermal range covering room temperature (RT) due to supercooling. This finding is notable given the fact that the N* phase possesses technologically significant optical properties. At RT, the N* phase displayed one of the iridescent colours characteristically caused by interference and diffraction of the reflected and scattered light. A comparative study reveals that the lengths of both the terminal chain and central spacer influence the clearing temperature of the dimers, and also the temperature range of the N* phase. The selective reflection measurements revealed that the pitch of the N* phase is either temperature sensitive or temperature insensitive. Temperature-dependent circular dichroism (CD) spectra were recorded for the planar texture of the N* phase formed by a dimer, as a representative case. The presence of an intense negative CD band suggests the left-handed screw sense of the N* phase helix.
Keywords: CD activity; cholesteric phase; dimers; liquid crystals; selective reflection